OGLE-2015-BLG-1609Lb: a sub-Jovian planet orbiting a low-mass stellar or brown dwarf host - Mróz, Mateusz Jan; Poleski, R.; Udalski, A.; Sumi, T.; Tsapras, Yiannis; Hundertmark, Markus; Pietrukowicz, P.; Szymański, M. K.; Skowron, J.; Mróz, P.; Gromadzki, M.; Iwanek, P.; et al. (Astronomy and astrophysics, 2025)
We present a comprehensive analysis of the planetary microlensing event OGLE-2015-BLG-1609. The planetary anomaly was detected by two survey telescopes, OGLE and MOA. Both surveys collected enough data over the planetary anomaly to enable an unambiguous planet detection. Such survey detections of planetary anomalies are needed to build a robust sample of planets, which could improve studies on the microlensing planetary occurrence rate by reducing biases and statistical uncertainties. In this work we examined different methods for modeling microlensing events using individual datasets. In particular, we incorporated a Galactic model prior to better constrain the poorly defined microlensing parallax. Ultimately, we fitted a comprehensive model to all available data, identifying three potential topologies, with two showing comparably high Bayesian evidence. Our analysis indicates that the host of the planet is either a brown dwarf, with a probability of 34%, or a low-mass stellar object (M dwarf), with a probability of 66%. The topology that provides the best fit to the data results in an extraordinary low host mass, M h = 0.025 +0.050 -0.012 M⊙, accompanied by an Earth-mass planet with M c = 1.9 +3.9 -1.0 M⊕.
Online veröffentlicht: 12. Juni 2025
Gesehen am 29.10.2025